Determination of some petrophysical properties of reservoir rocks in the Niger Delta (2015)
In formation evaluation, the knowledge of porosity, permeability and fluids saturation are very important in the determination of the hydrocarbon in place. These petro physical properties are necessary to understand the nature of the reservoir and help for proper field development planning. This was aimed at determining the petro physical properties (pore volume, bulk volume, grain volume, permeability and fluid saturation) of a reservoir from core plugs. A total of ten core plugs were used in this work. Archimedes immersion method was used in the determination of the bulk volume. Liquid saturation method was used in the determination of the porosity. The Dean-Stark extraction method was used in the determination of fluid saturation. From the results obtained in the core analysis, the sandstone reservoir has an average porosity of 14.9±5.1%, very good permeability with an average value of 349.77±0.3 mD and a very large water saturation value of 82±0.4%. Consequently the hydrocarbon saturation is approximately 18%. This implies that the formation is not commercially viable to develop based on the hydrocarbon saturation. The study shows that experimental work is one of the valid tools for making informed decisions on the development of a field in the petroleum industry and highlights the importance of the basic petrophysical properties in reservoir management.